Bayés' syndrome: Time to consider early anticoagulation? - Adrian Baranchuk; Bryce Alexander; Goksel Cinier; Manuel Martinez-selles; Ahmet Ilker Tekkesin; Roberto Elousa; Antoni Bayes De Luna (İstanbul Kuzey Klinikleri, 2018)
In the past few decades, extensive research has been conducted on atrial conduction disorders and their clinical relevance. An association between interatrial block (IAB) and supraventricular arrhythmias [most commonly atrial fibrillation (AF)] has been discovered and extensively investigated. We coined the term 'Bayés Syndrome' to describe this association, and the medical community has accepted the eponym in recognition to the scientist who discovered most of the aspects associated with it. In this non-systematic review, we will focus on the association between IAB and AF, with special emphasis on the value of the surface 12-lead ECG as a valid tool to predict AF.